Perkembangan Bahasa Anak Perempuan Usia 3 Tahun di Desa Teumpeun - Istiqamah, Istiqamah; Nurfazilah, Nurfazilah; Nazlina, Saskia Aulia; Ilmi, Nurul; Intan, Cut (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Language is a human communication system that is used to understand each other with certain goals. This research aims to find out the process of language development in three year old children. The method used in this research is a descriptive method with a qualitative approach. The results of the research found that Aqila can now say 2 to 4 words such as drink milk, Dad buy snacks. By using data collection techniques in the form of observation, interviews and documentation. The results of interviews with the child's parents and observing directly his language development showed that this child experienced language development according to the level at his age, including the words mother, father, sister, brother, milk, traveling. This research can conclude that Aqila often omits several phonemes or even adds phonemes to her vocabulary. Such as changing the consonant phoneme /k/ to consonant phoneme /t/, and changing the consonant phoneme /l/ to consonant phoneme /r/.